Caucasian validation of downstaging from IIB to IIA in T1N1M0 patients within the 9th edition of the non‐small cell lung cancer tumor‐node‐metastasis staging - Jingsheng Cai; Yun Li; Feng Yang (Cancer Medicine)
Abstract Background The 9th edition of the lung cancer tumor‐node‐metastasis (TNM) staging introduced adjustments, including the reclassification of T1N1M0 patients from stage IIB to IIA. This update used data mostly from Asian populations. However, the applicability of these adjustments to Caucasian patients remains uncertain. Methods Stage II non‐small cell lung cancer (NSCLC) patients from the Surveillance, Epidemiology, and End Results (SEER) database were included. Kaplan–Meier analysis with log‐rank testing compared overall survival (OS) and cancer‐specific survival (CSS). Propensity score matching (PSM) balanced baseline characteristics. The least absolute shrinkage and selection operator (LASSO)‐based Cox analyses identified prognostic factors. Results Among 10,470 eligible stage II NSCLC patients (median age: 69 years; male: 53.1%), there were 2736 in stage IIA, 2112 in IIA New, and 5622 in IIB groups. Before PSM, survival outcomes of stage IIA New patients were similar to those of stage IIA patients but better than those of stage IIB. After PSM, stage IIA New and IIB patients showed similar survival rates (OS, p = 0.276; CSS, p = 0.565). Conversely, stage IIA New patients had worse outcomes than stage IIA patients (OS, p < 0.001; CSS, p = 0.005). LASSO‐based Cox analyses confirmed stage IIA New patients had inferior prognosis compared to stage IIA patients (OS HR: 1 vs. 1.325, p < 0.001; CSS HR: 1 vs. 1.327, p < 0.001). Conclusions The downstaging of T1N1M0 patients from stage IIB to IIA in the 9th edition TNM staging remains unverified in Caucasians. Caution is warranted in assessing the staging and prognosis of these individuals. Further validation of our findings is necessary.